Dermatitis herpetiformis and diabetes mellitus. Issue 651 (January 1980) - Holt, S.; Blackwell, J. N.
Abstract : Three out of 4 patients with coexistent diabetes mellitus and dermatitis herpetiformis (DH) developed severe renal failure which resulted in death in 2 of them. Diabetes mellitus and DH may coexist more frequently than would occur by chance, and such patients may run an increased risk from severe renal complications of diabetes.